Validation of method in evaluating accident costs in palm oil plantation industries - Ahmad, Azizah (2018)
Introduction: Occupational accidents in agriculture are one of the high accident rates in Malaysia. Palm oil workers are facing risk due to the multiple agencies that cause injuries. Accidents and injuries in the workplace may give major impact on the company financial performance which is related to the cost of the accident. The objective of this study is to validate the new instrument in evaluating the accident cost in palm oil plantation industries. Methodology: This study used the retrospective cross sectional study design to examine accident cost, prevention cost and benefit of accident prevention incurred by employers related temporary disablement cases in palm oil plantation industries in Malaysia. The data was taken from Social Security Organization (SOCSO) and Ministry of Human Resource Malaysia where the accident report was reported. A total of 203 injured workers were chosen as respondent representing a total of 48 palm oil companies were selected all over Malaysia. For each occupational accident cases, the management representative and the injured worker were interviewed by using the new instrument in order to estimate the potential cost arises and incurred by the company. This questionnaire was reviewed by expert by using content validity index (CVI) method. The data were analyzed for validation, reliability, accident costing, prevention cost and benefit of accident prevention. Regression procedures in SPSS version 20 with p < 0.05 are used to identify the effectiveness of investment on safety. Result: Content validity study revealed that this instrument meets an excellent level of content validity. The overall content validity index of the instrument (ACPB-Q) using universal agreement approach was high value of the S-CVI which was 0.90 with content validity process identified three dimensions consists of the accident prevention items was S-CVI 1, accident cost was SCVI 0.9 and benefit of accident prevention was S-CVI 0.85. There were better agreements among experts on ACPB questionnaire. In Confirmatory Factor Analysis (CFA) results, the model fit indices are acceptable (RMSEA = 0.044) or slightly less than the good fit values (AIC = 18.774, CFI = 0.998, IFI = 0.998, and TLI = 0.995). The value of average variance extracted (AVE) was 0.605 and constructs reliability (CR) was 0.864. Both values met the criteria in the validation with relatively good construct validity and internal consistency of the model. The results for characteristic of accidents based on NADOPOD Malaysia shows the main types of injury was were others wounds (17%), the main types of accident were fall at the work place (44.33%), the main accident causation were working environment (35.47%) and the main location of injury were upper limb (35.96%). While, for the overall result of the accident cost based on accident characteristic shows the average amount of median under RM1200. The result of this study shows that the harvester category was shown to have the highest accident cost with mean at RM8787.99(±2300.16), as the percentage of the highest contributors to accidents was contributed by the cost of losing output. As conclusion, the total of occupational accident costs show score of median RM980(IQR274.00) with the output loss parameter gives the largest percentage of the accidents cost with mean value of RM7094.65(±2221.08). Coefficient analysis shows there is a strong, positive correlation between cost of accident prevention and benefit of accident prevention with a significant regression equation was found (F(1,48 ) = 163.78, p < .001), with r of 0.88. A value of r = 0.88 which shows the model fit and quite acceptable value for acceptance of model. The value of R square is 0.78 which is 78% explained variance in the dependent variable benefit of accident prevention does contribute by prevention cost of accidents. It predicted the benefit of accident prevention is equal to 21652.45 + 1.76x where the x represents the cost of accident prevention and is measured in Ringgit Malaysia. This suggested that the prevention cost of the accident is a good predictor of the benefit of cost prevention. Conclusion: The validity study helps researchers better understand, use and criticize research instruments with a more accurate approach and realize that the instruments are suitable for the construct, population under study, and socio-cultural background in which the study is carried out. The data of accident cost, prevention and benefit can provide the proposed equation formulas as a guide to employer's decision making regarding accident prevention which potentially leads to the company economic consequences and their effectiveness of safety and health management.